(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
In the article, the issues of strengthening the reproductive health of the population, maintaining the statistical indicators of women of childbearing age in an embodied/integrated manner, reducing maternal and infant mortality through regular case management, and protecting motherhood and childhood are discussed. This case–management healthcare system is intended for primary midwives, patronage nurses, heads of OP/OShP, KTPP, UASh specialists, reproductive specialists, internal pharmacy managers, chief specialists of district and city OB and BMQ, chief obstetrician–gynecologists and specialists of regional OB and BMQ management. and intended for social workers.